Fuzzy Logic based control system and Artificial Intelligence in Industrial Automation. Issue 1 (November 2020) - Deepa, R; Sri Rakshitha, A K; Gopala Krishnan, V
Abstract: Amidst the AI driven world, the Automation plays a major role in every sector. Usually the control systems in industries are manually controlled in unpredictable conditions. We are in need of a human to control a system. In this affair an AI trained machine acts as a human replica to drive it fully automated. The highly labor-intensive industries can be benefited by the use of Artificial Intelligence in the automation part, this reduces the human errors and safeguard them from risky areas. The fuzzy based PID controller is used here because it acts as Human-in-the-loop behind the whole process. This helps in tuning the PID controller to set a desired value which enhances the gains, adding to that it gives a high accuracy and brings up more flexibility in changing the rules. The result which is obtained is simulated in MATLAB with overshoot difference.